2021
DOI: 10.29228/sobider.52147
|View full text |Cite
|
Sign up to set email alerts
|

Integration From the Perspective of Children With Special Needs: A Phenomenological Study

Abstract: This study was conducted to investigate the implications of the experience of integration for children with special needs. The study was conducted using the qualitative research method of phenomenology. The study group comprised integration students with specific learning disability, currently attending primary and secondary school in Ankara. A semi-structured interview form was used within the scope of the research. The interviews, which were turned into written documents, were coded in the MaxQDA program in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Previous research has highlighted the importance of recognizing difficulties in socialemotional development as early indicators of potential issues (İzoğlu-Tok & Doğan, 2022;Sakellariou et al, 2020;Tercan & Yıldız-Bıçakçı, 2018). In particular, a qualitative study by İzoğlu-Tok et al (2021) found that children with SLD felt marginalized and invisible due to experiences of bullying, with participation in mainstreaming services often equating to feelings of "rejection" and "not belonging." Reflecting on both our findings and those of previous studies, children were frequently described as "silent," "vulnerable," "sensitive," and "introverted."…”
Section: Overview Of Developmental Symptomsmentioning
confidence: 99%
“…Previous research has highlighted the importance of recognizing difficulties in socialemotional development as early indicators of potential issues (İzoğlu-Tok & Doğan, 2022;Sakellariou et al, 2020;Tercan & Yıldız-Bıçakçı, 2018). In particular, a qualitative study by İzoğlu-Tok et al (2021) found that children with SLD felt marginalized and invisible due to experiences of bullying, with participation in mainstreaming services often equating to feelings of "rejection" and "not belonging." Reflecting on both our findings and those of previous studies, children were frequently described as "silent," "vulnerable," "sensitive," and "introverted."…”
Section: Overview Of Developmental Symptomsmentioning
confidence: 99%